PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH PESERTA DIDIK MATERI GERAK DENGAN PEMBELAJARAN BERBASIS MASALAH - Nurlaela; Widiasih (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Terbuka, 2023)
The low ability to solve problems in the motion of objects material and its application from theresult of problem- solving ability (50% under the KKM) encourages researchers to gain improvements tolearning. Learning improvement aims to improve students' problem-solving skills in science learning,especially motion material. For teachers as an effort to increase performance by using a problem-basedlearning approach, the learning process will become meaningful, and students will become active inlearning. After applying the problem-based learning model and using demonstration and experimentalmethods in cycles 1 and 2, it turned out that students were motivated to learn, and 83% of studentsachieved KKM. The conclusion is the application of the problem-based learning model in science learningabout the motion of objects and its application can improve the problem-solving abilities of class VIIIstudents.